2022
DOI: 10.3390/su142113748
|View full text |Cite
|
Sign up to set email alerts
|

Social Capital Inequality According to Hukou in Unequal Economic Environments in China

Abstract: China is experiencing an increase in socioeconomic inequality in comparison to the global trend. Employing the hukou registration as a focal point, this study seeks to examine social capital differences between developed and underdeveloped regions in China. As the data for the analysis were from the China Family Panel Studies, social capital was measured by social trust, participation, and networks. The Gini coefficient, a measure of economic inequality, was calculated for 25 different provinces in China in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Although MacKinnon [ 74 ] and Preacher and Hayes [ 75 ] emphasize the causal relationship between independent variables and mediators in the mediation effect method, the relationship between economic inequality and social capital is ambiguous based on the social capital components. For example, Lyu et al [ 76 ] found that social trust and networks are lower in neighborhoods with greater economic inequality, but the effect is not statistically significant for social participation. As such, because the relationship between economic inequality and social capital tends to vary depending on the factors, this study analyzes daily mental stress according to economic inequality and social capital using moderation effects rather than mediation effects.…”
Section: Methodsmentioning
confidence: 99%
“…Although MacKinnon [ 74 ] and Preacher and Hayes [ 75 ] emphasize the causal relationship between independent variables and mediators in the mediation effect method, the relationship between economic inequality and social capital is ambiguous based on the social capital components. For example, Lyu et al [ 76 ] found that social trust and networks are lower in neighborhoods with greater economic inequality, but the effect is not statistically significant for social participation. As such, because the relationship between economic inequality and social capital tends to vary depending on the factors, this study analyzes daily mental stress according to economic inequality and social capital using moderation effects rather than mediation effects.…”
Section: Methodsmentioning
confidence: 99%
“…The inequality of economic development is of critical significance to economic development and is a concern for scholars worldwide. Since the 1980s, the foreign-related scholars' research literature on economic inequality has mushroomed [8][9][10][11][12][13], and then relevant domestic studies began to emerge rapidly. As indicated by the existing research results, numerous factors cause China's regional development gap to widen constantly, and they can roughly fall into two types.…”
Section: Literature Reviewmentioning
confidence: 99%
“…If the Soviet Union aid project leads to a considerable amount of regional capital inflow, β 2 is significantly higher than zero. Model (10) represents the regression result of the second stage, and its setting is the same as that of Model (7), except that the core explanatory variable capital deepening refers to the estimated value of the regression of the first stage. The regression results of the two stages are listed in Table 3.…”
Section: Robustness Test 421 Endogenous Testmentioning
confidence: 99%